PSYCHOLOGICAL BARRIERS AND THEIR INFLUENCE TOWARDS STUDENTS’ SPEAKING ABILITY - Wulandari, Wahyuni; Juddah, Abu Bakar; Sunubi, Abdul Haris (Prodi Tadris Bahasa Inggris STAIN Parepare (IAIN Parepare), 2018)
The purpose of the research was to find out the influence of psychological barriers experienced by the students towards their speaking ability. This research employed quantitative descriptive method. The instruments used to collect data were questionnaire and speaking test. The subjects of the research were the students of class VIII.4 academic year 2016/2017. The data analysis revealed that the students experienced the medium level of psychological barriers. It was shown by the average score of the questionnaire which was 47. Besides, the students? ability in speaking English need to improve. The average score of the speaking test was 45. The simple linier regression formula discovered that t count = 1,21 > t table = 0,85. Hence, Ho was rejected and Ha was accepted which means that there was a significant influence of the students? psychological barriers towards their speaking ability.